A Bodhisattva on Horseback: Buddhist Ethics and Pragmatism in Northern Thailand - Cohen, Paul T. (The Australian journal of anthropology, 1983)
In Theravada Buddhism temporal power is viewed as indispensible to the creation of political and economic conditions for spiritiual advancement. But it is a necessary evil. The Buddhist response to the misuse of power is to subordinate it to Buddhist ethics and to deny politics autonomy from religion. Yut, in Buddhist Thailand, there is another tradition which justifies pragmatism and even the use of force. This paper concerns a local leader in Northern Thailand who has attempted to achieve some sort of balance between these to contradictory traditions – a goal that has proved elusive.